2000
DOI: 10.1161/01.cir.102.2.149
|View full text |Cite
|
Sign up to set email alerts
|

Oral Glycoprotein IIb/IIIa Inhibition With Orbofiban in Patients With Unstable Coronary Syndromes (OPUS-TIMI 16) Trial

Abstract: Background —Although intravenous glycoprotein IIb/IIIa inhibitors are beneficial in patients with acute coronary syndromes, prolonged oral IIb/IIIa inhibition might provide an additional reduction in recurrent events. Methods and Results —Investigators at 888 hospitals in 29 countries enrolled 10 288 patients with acute coronary syndromes, which was defined as ischemic pain at rest within 72 hours of randomization, associated with positive cardiac marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
142
1
7

Year Published

2000
2000
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 263 publications
(155 citation statements)
references
References 29 publications
5
142
1
7
Order By: Relevance
“…Each of the components of this end point was adjudicated by an independent clinical events committee using standard TIMI definitions. 26 Baseline biomarkers were considered positive if above an accepted, prespecified cut point based on prior work. Specifically, cut points for positive biomarkers were 0.01 ng/mL for cardiac TnT, 14 0.1 ng/mL for TnI, 14 15 mg/L for hs-CRP, 21 and 80 pg/mL for BNP.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of the components of this end point was adjudicated by an independent clinical events committee using standard TIMI definitions. 26 Baseline biomarkers were considered positive if above an accepted, prespecified cut point based on prior work. Specifically, cut points for positive biomarkers were 0.01 ng/mL for cardiac TnT, 14 0.1 ng/mL for TnI, 14 15 mg/L for hs-CRP, 21 and 80 pg/mL for BNP.…”
Section: Methodsmentioning
confidence: 99%
“…Details of the TIMI 11 studies have been published elsewhere 28,29 ; each compared unfractionated heparin to enoxaparin. Details of the OPUS-TIMI 16 trial, 26 a randomized, placebocontrolled trial of orbofiban (oral glycoprotein IIb/IIIa inhibitor) in ACS have also been published previously. The present analysis was limited to patients with UA/NSTEMI.…”
Section: Methodsmentioning
confidence: 99%
“…Uma análise de subgrupos do estudo OPUS TIMI 16 revelou que níveis mais elevados de peptídeo natriurético tipo-B estavam associados com estenoses coronarianas > 50% e com testes de esforço positivo (p<0,001) 31 .…”
Section: Peptídeo Natriurético Tipo-b E Cardiopatia Isquêmicaunclassified
“…The protocol and main results of the OPUS-TIMI-16 trial have been reported previously. 11 Briefly, the study was designed to compare two doses of the oral glycoprotein IIb/IIIa platelet receptor blocker, orbofiban, with placebo for management of patients with ACS. In all, 10,302 patients were randomized into the trial within 72 h of the onset of ACS from October 10, 1997, to November 5, 1998.…”
Section: Introductionmentioning
confidence: 99%
“…In all, 10,302 patients were randomized into the trial within 72 h of the onset of ACS from October 10, 1997, to November 5, 1998. The exclusion criteria were reported previously 11 and included patients with cardiogenic shock. All patients received aspirin; other therapy was at the discretion of the attending physician.…”
Section: Introductionmentioning
confidence: 99%